Hukum Ketahanan Pangan : Studi Implementasi Inpres Nomor 5 Tahun 2011 Tentang Pengamanan Produksi Beras Nasional Dalam Menghadapi Kondisi Iklim Ekstrim Oleh Babinsa Di Kabupaten Ngawi - Sigit Sapto Nugroho; Hery Sumanto; Bambang Sukarjono (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2020)
The specific purpose of this study is to describe the implementation of Presidential Instruction Number 5 of 2011 concerning Safeguarding National Rice Production in Facing Extreme Climate Conditions by Babinsa in the context of food self-sufficiency in Ngawi Regency. This study uses an empirical legal research method which is a legal research method that seeks to see the law in the real sense or, examines how law works in society. Research location in Ngawi Regency. Based on the results of research and discussion shows that the Implementation of Presidential Instruction No. 5 of 2011 by Babinsa in the context of food self-sufficiency in Ngawi Regency that emphasizes the role of Babinsa as a motivator, facilitator, dynamic and there are those who are able to become innovators for farmer groups in the field. As for the way of Babinsa Kodim 0805 Ngawi in carrying out food self-sufficiency by: 1) Moving and motivating farmers to carry out rehabilitation of tertiary irrigation networks, sundep pest control movements, rat pest control movements, and the harvest harvest movement. 2) Carry out support in escorting drooping subsidized rice seedand securing drooping subsidized fertilizer. 3) Carry out oversight of administrative filing and distribution of assistance to beneficiaries, as well as supervise the identification, data collection and technical reporting of the implementation of activities.